Examining empathy and responsiveness in a high-service context. Issue 12 (15th August 2019) - Murray, John; Elms, Jonathan; Curran, Mike
Abstract : Purpose: The delivery of high-quality service is critical for the success, or otherwise, of many retailers. However, despite calls to examine the efficacy of the dimensions of quality in different service contexts, it is still largely unknown how dimensions such as empathy and responsiveness interact to determine consumers' perceptions of service quality. Recent research also suggests that loyalty strategies may not be equally effective across all services contexts. The purpose of this paper is, therefore, to contribute to the service quality literature by providing a better understanding of how marketing strategy is effectively operationalised into improved services and consumer loyalty in physical stores. Design/methodology/approach: Consumers from ten stores of one pharmacy retailer were surveyed. The retailer provides high-service levels at present and is examining ways of how to deliver a better quality service to its prescription and non-prescription account holding consumers. By examining consumer loyalties in high-services contexts in pharmacy retailing, the authors also propose how retailers in other sectors can learn to operationalise services quality into increased loyalties. Findings: The findings of this research demonstrate that empathy, rather than responsiveness, is more important in a high service delivery context such as pharmacy retailing. Non-prescription account holding and non-store loyal consumers also do not perceive that high service responsiveness is compromised by offering of a highly empathetic (and possibly more time consuming) service by the retailer. Originality/value: These findings present specific implications for retailers in the development of consumer loyalty in a high-service context. Moreover, the findings of this research also illustrate how retailers can more effectively target their investments in service design to enhance service quality and consumer loyalty.